A systematic review and meta-analysis on computed tomography angiography mapping for deep inferior epigastric perforator flap breast reconstruction - Rupra, Roshan S.; Ruccia, Francesca; Daneshi, Kian; Aftab, Fatema; Yousif, Yousif F.; Khan, Gul R.; Dehnadi, Sina; AlSaidi, Yaqoob H.; Maggialetti, Nicola; Lorusso, Giovanni; Yan, Maria; Khajuria, Ankur (Frontiers in Oncology, 2025)
BackgroundBreast cancer remains the most prevalent cancer among women globally, necessitating effective reconstructive options post-mastectomy. The deep inferior epigastric perforator (DIEP) flap is the gold standard for autologous breast reconstruction, though anatomical variability of perforators presents surgical challenges. Computed tomography angiography (CTA) has been proposed to enhance preoperative planning and reduce operative time. The aim of this study is to identify how CTA affects surgical outcomes in autologous breast reconstruction.MethodsA systematic review and meta-analysis (PROSPERO: CRD42024596646) were conducted per PRISMA guidelines. A comprehensive search of six databases identified studies comparing CTA with non-CTA imaging for DIEP flap reconstruction. Primary outcomes included operative time and flap loss rates. Risk of bias was assessed using ROBINS-I and RoB2, with quality appraised via AMSTAR-2 and GRADE.ResultsEighteen studies (3870 patients, 4283 flaps) were included. CTA guidance reduced unilateral flap operative time (mean 304.98 min vs. 390.18 min, CI −12.9 to 5.7; P = 0.2367), as well as partial and total flap loss rates (OR: 0.26, 95% CI: 0.14–0.47; OR: 0.30, 95% CI: 0.13–0.68). High heterogeneity (I² = 98.7%) limited generalizability. Prior reviews showed limitations in study design integrity, whereas this study achieved a high-confidence rating.ConclusionsPreoperative CTA improves surgical outcomes in DIEP flap reconstruction, though evidence quality is variable. Future research should compare CTA with MRA, assess cost-effectiveness, integrate AI-assisted imaging, and explore MRI-based protocols for optimized preoperative planning in microsurgical breast cancer reconstruction and enhanced oncologic care delivery.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024596646, idenitifier CRD42024596646.